Mechanisms to support transition to pupils with special educational needs (SEN) at school and the role of headmaster in this process - Nakhutsrishvili, Nino ("Intercultural Dialogues" Transactions, 2023)
Effectiveness of learning and teaching and pupil’s academic achievement in general educational school is relied on various factors. It’s obvious that every success or failure has its own causes and preconditions. Though, in the case of failure of primary level pupil transition process sometimes stays out of focus which is an essential determinant precondition of successful learning of a pupil. Transition is reflected individually in each pupil’s psyche. It’s true that it carries developmental function, but at the same time it creates stressful background and isn’t an easy process for a child. That’s why it really requires the implementation of certain supportive and effective mechanisms and accordingly creation of conditions and relationships at school. When the case refers to SEN pupil we face more challenges and there is greater need to implement each component of transition appropriately. In planning and implementation of this process as well as creation correct strategy of a school its headmaster bears major role. To evaluate public school strategies in this direction and to investigate existing reality at schools we have presented research results of headmasters of Telavi municipality public schools which made clear that besides their positive attitude and deep understanding to support transition process there still exists some gaps which needs to be improved on time. It refers to development of inner policy to support SEN pupils transition (with appropriate regulations) as well as creation SEN pupils transition program, implementation effective activities to communicate with parents and to support transition, activities to create and adjust school environment and infrastructure to pupils’ needs (among them SEN pupils), implementation effective mechanism to cooperate with pre - school institutions, etc. Even the research in one of the schools in the municipality allows us to talk about existing reality and conclude that there is still a lot of work to do in the transition process and the work in this direction should become one of the strategic directions at schools.